NEXT GENERATION ORAL PrEP: BEYOND TENOFOVIR - Abraham, Bisrat K. (2012)
PURPOSE: Clinical trials of oral pre-exposure prophylaxis (PrEP) have focused testing on regimens of tenofovir (TDF) with or without emtricitabine (FTC). However, TDF may be associated with toxicities (renal, bone) and FTC may select for drug resistance. In this review, we discuss agents that might serve as alternatives to TDF/FTC for HIV prevention. RECENT FINDINGS: Several drug characteristics are important to consider when selecting agents for PrEP with the most critical being safety, tolerability, adequate penetration into target tissues, prevention of HIV infection, and long lasting activity with convenient dosing. With these factors in mind, we review several potentially useful agents for PrEP. The first group includes drugs that are already FDA-approved (maraviroc, raltegravir) with attributes that make them attractive for PrEP. The second groups of drugs include investigational agents with long-lasting activities that are being developed in parenteral form (rilpivirine-long acting, S/GSK 1265744, ibalizumab). SUMMARY: Current research suggests there will be a broader array of PrEP drugs to choose from in the near future, thereby giving clinicians the flexibility to select agents that best suit the needs of their patient population.